Aquaponic Biofloc Technology by Swamp Bacteria Probiotic for Clarias Catfish Rearing - Marini Wijayanti; Mohamad Amin; Tanbiyaskur Tanbiyaskur; Dade Jubaedah; Kukuh Jaya; M Aiman Ziyad; Marsi Marsi (Department of Aquaculture, 2021)
Conventional catfish culture in Ogan Ilir (OI) have not optimal production, it can be increased by biofloc and aquaponics with local swamp bacteria as a starter. The purpose of this study was to apply biofloc technology and a combination of aquaponic-biofloc to increase the productivity of catfish (Clarias sp.) rearing. The study used two ponds, a biofloc circular pond and a combined biofloc and aquaponic (biofloqua) for two months. The results of the specific growth rate of fish in the aquaponic biofloc system were higher than that of the biofloc system alone. The survival of the fish during two rearing months of the Biofloqua system was 100% while the Biofloc system was 92-96%. The water quality data that measured were temperature, 30.3–31.9oC, Dissolved oxygen 4.5–7.2 mg.l-1, pH 6-7, and ammonia concentration 0.27-0.71 mg.l-1 in the biofloc system and 29.5-31.3oC, 4.7-7.4 mg.l-1, pH 6-7, 0.20-0.53 mg.l-1 in biofloqua system, respectively. The floc volume formation rate in the biofloc system alone reached 1.1 ml.l-1 per day, which was above the floc formation rate for the biofloqua system 0.42 ml.l-1 per day, due to the use of nutrients for plant growth. The combination of biofloc and aquaponics showed more optimal growth performance and both were efficient in feed (Food Conversion Ratio / FCR <1.00). Although the results of the 5% level t test showed no difference in the performance of the aquaculture biota between the two systems, Biofloqua can be an alternative to increase fish farmer income by harvesting vegetables and fish together.